PENGELOLAAN DAN PEMANFAATAN WAKAF TANAH DAN BANGUNAN - NURHIDAYANI NURHIDAYANI; MUAIDY YASIN; BUSAINI BUSAINI (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The theme of the article is "economy based on the principles of Islam". The research explores how the management and utilization of endowment (waqf) of land and building at Dhompet Amal Ibnu Abbas (DASI) West Nusa Tenggara. Method of theresearch is qualitative using observation, interview and documentation instrument. Result of the research shows that the Nazhir and Wakif’s understanding in the management and utilization of waqf of land and building is still based ontrust management. Waqf management by nazhir is still traditional which the waqf law No. 41 year 2004 is not implemented completely. The Nazhir of waqf only fulfills the moral requirement of managing waqf as a trustworthy institution, but the institution has not yet fulfilled management and business requirement. In term of utilization, the institution is already qualified with the law of waqf which aims helping poor family (dhuafa) and orphans welfare. Therefore, waqf management institution is expected to improve human resources in managing waqf productively in order to attract society to do waqf, support from religious leaders and the government in this case the Ministry of Religion should be more aggressive in mobilizing waqf program, especially in terms of administration of waqf assets. They should socialize and nurture waqf manager (nazhir) actively to grow and provide wide benefits for social welfare, especially dhuafa family and orphans.